Government Spending on Economic Growth in North Sumatera - Riky Aulia Rachman Marpaung; Rika Angraini; Salsabilla Nurul Izza; Diki Purnomo; Rizky Fadly (Outline Journal of Economic Studies, 2023)
This study aims to determine and analyze the effect of government spending on economic growth in North Sumatra Tabun 2017-2021. The research method used in this study is secondary data. The data taken is data published or obtained by the Central Statistics Agency (BPS). In this study, in conducting data analysis techniques, namely using the OLS (Ordinary Least Square) method using the Eviews 10 analysis tool. The result of this study is that simultaneously the variable government expenditure has an insignificant influence on the economic growth variable for 2017-2021 in North Sumatra Province. The variable government expenditure partially has a positive and insignificant influence on economic growth in North Sumatra Province. The Government Expenditure Variable (X) has a simultaneous influence on the Economic Growth variable (Y) of 56% and the remaining 44% is influenced by other unincluded variables.